Electroreduction of Some Substituted Hydrazones on Platinum Electrode in Dimethylformamide - Ozel, Ayca Demirel; Durmus, Zehra; Yilmaz, Ibrahim; Cukurovali, Alaaddin; Kilic, Esma (Slovensko Kemijsko Drustvo, 2009)
The electrochemical behaviors of 4-(1-phenyl-1-methylcyclobutane-3-yl)-2-(2-hydroxybenzylidenehydrazino)thiazole (I), 4-(1-p-xylene-1-methylcyclobutane-3-yl)-2-(2-hydroxybenzylidenehydrazino)thiazole (II), 4-(1-mesytylene-1-methylcyclobutane-3-yl)-2-(2-hydroxybenzylidenehydrazino)thiazole (III), 4-(1-phenyl-1-methylcyclobutane-3-yl)-2(2-hydroxy-5-bromobenzylidenehydrazino)thiazole (IV), 4-(1-phenyl-1-1-methylcyclobutane-3-yl)-2-(2-hydroxy-3metoxybenzylidenehydrazino)thiazole (V), 4-(1-phenyl-1-methylcyclobutane-3-yl)-2-( 2,4- dihydroxybenzylidenehydrazino)thiazole (VI) were investigated by cyclic voltammetry (CV), controlled potential electrolysis, and chronoamperometry (CA) techniques in the presence of 0.10 M tetrabutylammonium tetrafluoroborate (TBATFB) in dimethylformamide (DMF) at platinum electrode. Hydrazones display two cathodic peaks at about -1.60 V and -2.20 V. Diffusion coefficients and the number of electrons transferred were calculated by using an ultramicro electrode (UME). Standard heterogeneous rate constants for reduction were calculated by Klingler-Kochi technique. Electrochemical reduction mechanism of these hydrazones was also proposed that hydrazones seemed to follow an ECEC mechanism corresponding with irreversible electron transfer steps. Due to the widespread use of hydrazones in drug production, the redox properties of these hydrazones are thought to be useful for enlightening the metabolic fate of the drug containing hydrazones or its in vivo redox properties or pharmacological activity.
Keywords: Hydrazones; thiazoles; electrochemical behavior; voltammetry; dimethylformamide